Interactive computer training to teach discrete‐trial instruction to undergraduates and special educators in Brazil: A replication and extension. Issue 4 (17th June 2016) - Higbee, Thomas S.; Aporta, Ana Paula; Resende, Alice; Nogueira, Mateus; Goyos, Celso; Pollard, Joy S.
Abstract : Discrete‐trial instruction (DTI) is a behavioral method of teaching young children with autism spectrum disorders (ASD) that has received a significant amount of research support. Because of a lack of qualified trainers in many areas of the world, researchers have recently begun to investigate alternative methods of training professionals to implement behavioral teaching procedures. One promising training method is interactive computer training, in which slides with recorded narration, video modeling, and embedded evaluation of content knowledge are used to teach a skill. In the present study, the effectiveness of interactive computer training developed by Pollard, Higbee, Akers, and Brodhead (2014), translated into Brazilian Portuguese, was evaluated with 4 university students (Study 1) and 4 special education teachers (Study 2). We evaluated the effectiveness of training on DTI skills during role‐plays with research assistants (Study 1) and during DTI sessions with young children with ASD (Studies 1 and 2) using a multiple baseline design. All participants acquired DTI skills after interactive computer training, although 5 of 8 participants required some form of feedback to reach proficiency. Responding generalized to untaught teaching programs for all participants. We evaluated maintenance with the teachers in Study 2, and DTI skills were maintained with 3 of 4 participants.